Drums of autumn - Gabaldon, Diana (Gabaldon, Diana. Outlander novels, 2014)
Scottish soldier Jamie Fraser and his wife, Claire Randall--a twentieth century doctor who has traveled two centuries back in time--find themselves in South Carolina on the eve of the American Revolution, where they must fight to save a young girl.